Association between N-terminal Pro-Brain Natriuretic Peptide levels, glomerular filtration rate, and heart failure in the Multi-Ethnic Study of Atherosclerosis. Issue 3 (2018) - Syed, Daneyal; Peshenko, Stephanie; Liu, Kiang; Durazo-Arvizu, Ramon; Rosas, Sylvia E; Shlipak, Michael; Sarnak, Mark; Jacobs, David; Sickovick, David; Lima, João; Kronmal, Richard; Kramer, Holly
No abstract available